Tamper localization for medical images using cyclic redundancy check (CRC) - Wan Nur Shakira Ain, Wan Ranizang (2013)
The thesis focuses on the implementation of medical image watermarking in Digital Imaging and Communications in Medicine (DICOM). DICOM is an important part of information technology infrastructure in a health institution. Watermarking can be used to authenticate medical images and provide the additional security needed on top of the existing security measures that were already in place. Watermarking methods applied to medical images should be tampered or if not, an area known as Region Of Interest (ROI) needs to be defined on the image to retain the original information. The watermarked image produced should have visual quality similar to its original one. This thesis proposed a tamper localization watermarking for medical images using Cyclic Redundancy Check (CRC). The confidentiality of medical images is increased by embedding CRC into image. I will use an ultrasound grayscale, CT-SCAN and also MRI. However, medical images require extreme care when embedding additional data within them because the additional information must not affect the image quality which leads to wrong diagnosis. So image is divided into ROI and Region Of Non Interest (RONI).